A Study of dental caries prevalence in 12–14 year old school children in Ibadan, Nigeria (2005)
The aim of the study was to determine dental caries prevalence among a representative sample of 12–14 year old school children in Ibadan, Nigeria with a view of determining Restorative Index and Met Need Index of the studied population. Dental caries was diagnosed according to the WHO method. Out of the 577 children in the age group, 65 children (11.2%) had dental caries experience as expressed with the DMFT index. More than 85% of the children were caries free. A mode of one DMFT was the highest score for the children although a 14-year-old pupil had DMFT score of 6. Female children had higher mean DMFT score of 2.03 1.13 compared with 1.78 1.0 for males (P 0.05). The Restorative Index (RI) and Met Need Index (MNI) for the children were very low as only the 14-year-old children had an RI of 3.45% and MNI of 0.11. Restorative Index reﬂects the restorative care of those who have suffered the disease and it is measured as a ratio of ﬁlled to ﬁlled plus decayed teeth percent that is F/F D percent. Met Need Index is an indication of treatment received by an individual and it is measured by the ratio of the mean missing plus ﬁlled teeth to mean decayed, missing and ﬁlled teeth that is M F/DMF. Since cost of management, which may be out of the reach of these children, has been identiﬁed as one of the factors militating against their receiving treatment, the result of this study suggest that oral health education with emphasis on correcting snacking habits of school children is desirable.